2013
DOI: 10.1097/ta.0b013e3182a685b0
|View full text |Cite
|
Sign up to set email alerts
|

The role of serious concomitant injuries in the treatment and outcome of pediatric severe traumatic brain injury

Abstract: Prognostic and epidemiologic study, level III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(24 citation statements)
references
References 18 publications
(29 reference statements)
1
23
0
Order By: Relevance
“…Focusing on other possible prognostic factors following pediatric TBI, we also found that the median PTS was significantly associated with mortality ( Table 1 ). A previous report of 180 patients [ 33 ] demonstrated that patients with serious concomitant injuries had fewer days off mechanical ventilation and longer hospital stay, although it did not significantly predict for mortality. In the above study, patients with serious concomitant injuries were most likely involved in motor vehicle accidents and had more severe TBI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Focusing on other possible prognostic factors following pediatric TBI, we also found that the median PTS was significantly associated with mortality ( Table 1 ). A previous report of 180 patients [ 33 ] demonstrated that patients with serious concomitant injuries had fewer days off mechanical ventilation and longer hospital stay, although it did not significantly predict for mortality. In the above study, patients with serious concomitant injuries were most likely involved in motor vehicle accidents and had more severe TBI [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous report of 180 patients [ 33 ] demonstrated that patients with serious concomitant injuries had fewer days off mechanical ventilation and longer hospital stay, although it did not significantly predict for mortality. In the above study, patients with serious concomitant injuries were most likely involved in motor vehicle accidents and had more severe TBI [ 33 ]. In another study of 100 adults with TBI, high grade concomitant injuries were associated with functional disability 18 months after the injury [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…18 A comprehensive workup should be performed to look for associated injuries, particularly closed head injury. Traumatic brain injury is a major cause of morbidity and mortality in the pediatric and adolescent polytrauma population, 19 and the utilization of flexible nailing must be performed with caution to prevent pulmonary and neurological compromise. 18 Additional orthopaedic injuries should be sought out and treated as well.…”
Section: Initial Assessmentmentioning
confidence: 99%
“…Patients were included in the study if the following criteria were met: Diagnosis of sTBI by computed tomography or magnetic resonance imaging; Glasgow Coma Scale (GCS) score of <8; and admittance to ICU within 8 h after injury (6). Exclusion criteria included combined brain complications, combined severe injury and patient mortality within seven days following injury (7).…”
Section: Methodsmentioning
confidence: 99%